Inside Cover: Aldol Condensations Catalyzed by Basic Anion‐Exchange Resins (ChemCatChem 23/2016). Issue 23 (7th December 2016) - Bonrath, Werner; Pressel, Yann; Schütz, Jan; Ferfecki, Erich; Topp, Klaus‐Dieter
Abstract : The Cover shows a cross aldol condensation over an ion‐exchange resin to form pseuodionone, which has a scent similar to that of violets. In their Full Paper, W. Bonrath et al. demonstrate condensations of various aldehydes with ketones in the presence of anionic (basic) ion‐exchange resins. The reactions were run in batch and continuous modes. Over 10 runs, no significant loss in activity and selectivity was observed for two of the tested resins. In continuous mode, a stable performance was noted for more than 15 h. More information can be found in the Full Paper by W. Bonrath et al. onpage 3584 in Issue 23, 2016 (DOI:10.1002/cctc.201600867 ).